The Resourceful earth : a response to Global 2000 - Simon, Julian Lincoln( 1932-); Kahn, Herman( 1922-1983.) (Oxford, OX ; New York, NY, USA: B. Blackwell, 1984)
"We are confident that the nature of the physical world permits continued improvement in humankind's economic lot in the long rung run, indefinitely. Of course there are always newly arising local problems, shortages and pollutions, due to climate or to increased population and income. Some times temporary large-scale problems arise. But the nature of the world's physical condition and the resilience in a well-functioning economic and social system enable us to overcome such problems, and the solutions usually leave us better off than if the problem had never arisen; that is the great lesson to be learned from human history. We are less optimistic, however, about the constraints currently imposed upon material progress by political and institutional forces, in conjunction with popularly-held beliefs and attitudes about natural resources and the environment...trends point towards deterioration rather than towards improvement..." -- Introduction.
Includes bibliographies and index.
Keywords: Ciencias sociales -- -- Metodología; Energiebronnen; Economic forecasting; Prévision économique.; Economische aspecten; Natuurlijke hulpbronnen; Economic history -- -- 1971-1990.; Histoire économique -- -- 1971-1990.; Ressources naturelles; Milieubeheer; Natural resources; Environment - Forecasts